Detection of mosaic chromosomal alterations in children with severe developmental disorders recruited to the DDD study - Ruth Y. Eberhardt; Caroline F. Wright; David R. FitzPatrick; Matthew E. Hurles; Helen V. Firth (Genetics in Medicine Open, 2023)
Purpose: Structural mosaicism has been previously implicated in developmental disorders. We aimed to identify rare mosaic chromosomal alterations (MCAs) in probands with severe undiagnosed developmental disorders. Methods: We identified MCAs in genotyping array data from 12,530 probands in the Deciphering Developmental Disorders study using mosaic chromosome alterations caller (MoChA). Results: We found 61 MCAs in 57 probands, many of these were tissue specific. In 23 of 26 (88.5%) cases for which the MCA was detected in saliva in which blood was also available for analysis, the MCA could not be detected in blood. The MCAs included 20 polysomies, comprising either 1 arm of a chromosome or a whole chromosome, for which we were able to show the timing of the error (25% mitosis, 40% meiosis I, and 35% meiosis II). Only 2 of 57 (3.5%) of the probands in whom we found MCAs had another likely genetic diagnosis identified by exome sequencing, despite an overall diagnostic yield of ∼40% across the cohort. Conclusion: Our results show that identification of MCAs provides candidate diagnoses for previously undiagnosed patients with developmental disorders, potentially explaining ∼0.45% of cases in the Deciphering Developmental Disorders study. Nearly 90% of these MCAs would have remained undetected by analyzing DNA from blood and no other tissue.